Hot corrosion studies on Ni-base superalloy at 650 °C under marine-like environment conditions using three salt mixture (Na2SO4 + NaCl + NaVO3). (April 2016) - Mannava, Venkateswararao; Rao, A. Sambasiva; Paulose, Neeta; Kamaraj, M.; Kottada, Ravi Sankar
Graphical abstract: Highlights: Addition of NaVO3 to Na2 SO4 –NaCl mixture (2SM) accelerates the oxidation kinetics. Formation of V2 O5 and O 2− ions from NaVO3 stimulates the basic fluxing mechanism. V2 O5 reacts with oxides (Cr2 O3, Fe2 O3 and NiO) and form corresponding vanadates. Cr-depletion layer forms due to formation of CrVO4, Cr-suiphides and Na2 Cr2 O7 . Repetitive formation of NaVO3 takes place by the combination of V2 O5 and Na2 SO4 . Abstract: The oxidation behavior of GTMSU718 alloy with 87.5 wt.% Na2 SO4  + 5 wt.% NaCl + 7.5 wt.% NaVO3 (3SM) was studied at 650 °C. Cyclic oxidation studies with 3SM show more weight gain than 2SM (90 wt.% Na2 SO4  + 10 wt.% NaCl). It indicates that NaVO3 accelerates the oxidation behavior. Isothermal studies show a repetitive NaVO3 formation by combination of V2 O5 and Na2 SO4 until Na2 SO4 is exhausted. Cr depletion layer occurs due to formation of Cr-sulphides, CrVO4 and liberation of Na2 Cr2 O7 . Based on the detailed critical analysis, a plausible hot corrosion mechanism with 3SM was analysed to be basic fluxing mechanism, in parallel with sulphidation followed by oxidation.